Ang "Noli Me Tangere" - Rizal, Jose (Cultural Center of the Philippines, 1992)
An adaptation of the novel of Dr. Jose Rizal on Philippine nationalism. This drama series exposes the abusive powers of the Spanish rulers in the Philippines, in particular the Spanish priests.